Nitrogen-doped carbon-based composite electrode material and preparation method and application thereof
By immersing the melamine sponge in a mixed suspension of activated carbon, conductive agent and binder, drying and calcining under an absorptive atmosphere, a nitrogen-doped carbon-based composite electrode material is prepared, which solves the problems of complicated preparation steps, low uniformity of nitrogen doping, insufficient mechanical strength and low density in the prior art, and achieves efficient nitrogen doping and self-supporting performance.
Patent Information
- Application Number
- CN202311203369.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-18
AI Technical Summary
The preparation steps for existing nitrogen-doped carbon-based self-supporting electrodes are complicated, the nitrogen element doping uniformity is low, and the post-activation treatment causes the electrode mechanical strength to be insufficient and the electrode density is low.
A nitrogen-doped carbon-based composite electrode material was prepared by immersing a melamine sponge in a mixed suspension of activated carbon, conductive agent and binder, drying and calcining under an absorptive atmosphere.
The nitrogen doping level of the electrode material is improved, the self-support function of the electrode is realized, the mass transfer efficiency of the electrode is improved, and the mechanical strength and density of the electrode are improved.
Smart Images

Figure CN119650317A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nitrogen-doped carbon-based composite electrode material and a preparation method and application thereof, belonging to the technical field of carbon materials. Background Art
[0002] The self-supported electrode (Self-Supported Electrode) is used directly as an electrode material without the need for additional current collectors and electrode assembly processes. It has good mechanical properties and higher mass transfer efficiency. It can be freely cut to achieve electrode preparation of different sizes and scales, which makes up for the shortcomings of traditional powder electrode materials in the above characteristics. It can be widely used in flexible electrodes, compressible electrodes, and capacitor deionization device electrodes for energy storage devices such as supercapacitors and lithium-sulfur batteries. It has become a research hotspot in recent years. At present, most self-supporting electrodes exist in the form of thin films and porous foams. On the other hand, nitrogen doping has been proven to be an important means to increase electrode capacity and improve electrode interface properties (such as hydrophilicity) (J.Mater.Chem.A, 2018, 6, 17730). It can be achieved by post-processing of the material or in-situ doping using a nitrogen-rich precursor for one-step carbonization.
[0003] Melamine sponge, as a nitrogen-rich material with a three-dimensional pore structure (high porosity, >98%), is an important raw material for the preparation of nitrogen-doped self-supporting electrodes.
[0004] CN114053996A discloses an integrally formed nitrogen-containing block porous carbon material and its preparation method and application. The method immerses the melamine sponge in a glucose solution, freeze-dries it and carbonizes it, and then activates it with carbon dioxide to prepare an integrally formed nitrogen-containing block porous carbon material. However, the method adopts a solution impregnation method, and the actual loaded glucose mass after the solution is dried is low, and the glucose carbonization yield is only 30%, resulting in a low overall density of the prepared material; at the same time, the method adopts a post-activation treatment to increase the specific surface area of the material, but the carbonized melamine skeleton is further broken, and the mechanical strength is greatly reduced.
[0005] CN113223862A discloses an activated sponge capacitor material and its preparation method and application. The method carbonizes melamine sponge, then impregnates dopamine graphene oxide aqueous solution, and then carbonizes and activates it after drying to obtain a nitrogen-doped electrode. However, the dopamine and graphene oxide used in the method are both high-value raw materials, the production cost is high, and the specific surface area of the prepared electrode is low.
[0006] CN108074751A discloses a flexible three-dimensional porous carbon material and its preparation method and application. In this method, coal tar and potassium hydroxide are dissolved and then impregnated into melamine sponge, and then carbonized and activated to obtain a nitrogen-doped flexible three-dimensional porous electrode material. However, the potassium hydroxide used in this method has a very strong etching effect. Although the obtained electrode material has a large specific surface area, the mechanical strength of the electrode is greatly damaged.
[0007] CN105826562A discloses a nitrogen-doped carbon flexible paper and a preparation method and application thereof. The method oxidizes melamine sponge, compresses and carbonizes it to obtain a flexible nitrogen-doped porous material. The preparation process of the method is simple, but the specific surface area of the prepared material is too low to achieve energy storage application.
[0008] The carbonization temperature effect on the electrochemical performance of nitrogen-doped carbon monoliths (J.Electracta.2017.05.016) used melamine sponge as a capacitor electrode after direct carbonization. The specific surface area of the electrode is too low (<30m 2 / g), which has poor performance in practical energy storage applications.
[0009] Developing a new type of nitrogen-doped carbon-based composite electrode material and its preparation method is still one of the urgent problems to be solved in this field. Summary of the invention
[0010] In order to solve the above technical problems, the purpose of the present invention is to provide a nitrogen-doped carbon-based composite electrode material and its preparation method and application. The technical solution of the present invention can improve the nitrogen doping level of the electrode material, realize the self-supporting function of the electrode, and improve the mass transfer efficiency of the electrode.
[0011] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a nitrogen-doped carbon-based composite electrode material, which comprises the following steps:
[0012] The melamine sponge is immersed in a suspension formed by mixing activated carbon, a conductive agent, a binder and a solvent, and the immersed melamine sponge is dried to obtain a composite precursor; the composite precursor is calcined in an oxygen-free atmosphere, and the nitrogen-doped carbon-based composite electrode material is obtained after cooling;
[0013] Wherein, based on the total mass of activated carbon, conductive agent and binder as 100%, the amount of activated carbon is 50-93%, the amount of conductive agent is 2-30%, and the amount of binder is 5-20%.
[0014] In the above preparation method, preferably, the density of the melamine sponge is 4 to 20 kg / m 3 The opening rate is 95-99.8%.
[0015] In the above preparation method, preferably, the specific surface area of the activated carbon is 200 to 4000 m 2 / g, particle size is 2-100 μm (measured in D50 diameter), and the pore volume of micropores with pore size less than 2 nm is 0.3-0.9 cm 3 / g, total pore volume is 0.3~1.5cm 3 More preferably, the specific surface area of the activated carbon is 800 to 2000 m 2 / g, the particle size is 6-20 μm (measured in D50 diameter), and the pore volume of micropores with a pore size less than 2 nm is 0.45-0.8 cm 3 / g, total pore volume is 0.5~1.5cm 3 / g.
[0016] In the above preparation method, preferably, the conductive agent includes one or a combination of carbon black, graphene and graphite.
[0017] In the above preparation method, preferably, the binder includes one or a combination of polyvinylidene fluoride, carboxymethyl cellulose, polytetrafluoroethylene, styrene-butadiene latex and polyvinyl alcohol.
[0018] In the above preparation method, preferably, the solid content of the suspension is 5 to 50% by volume.
[0019] In the above preparation method, preferably, the activated carbon, conductive agent, binder and solvent are uniformly mixed and dispersed to form a suspension, and the uniform mixing and dispersion method includes one or a combination of stirring mixing, ultrasound-assisted mixing and vacuum-assisted mixing.
[0020] In the above preparation method, preferably, the melamine sponge is immersed in the suspension by ultrasound-assisted dipping.
[0021] In the above preparation method, preferably, the melamine sponge is immersed in the suspension for 2 to 30 minutes.
[0022] In the above preparation method, preferably, the mass ratio of the melamine sponge to the activated carbon in the suspension is 1:100 to 1:1000.
[0023] In the above preparation method, preferably, in the composite precursor, the mass ratio of melamine sponge to activated carbon is 1:0.5 to 1:10.
[0024] In the above preparation method, preferably, the method of controlling the calcination atmosphere to be an anaerobic atmosphere includes: placing the composite precursor in a calcination furnace, first using a vacuum system to evacuate the air in the calcination furnace, and then introducing a non-oxidizing gas to completely replace the air in the pores of the composite precursor. More preferably, the non-oxidizing gas can be introduced repeatedly for several times.
[0025] In the above preparation method, preferably, the non-oxidizing gas includes one or a combination of nitrogen, argon, carbon dioxide and helium.
[0026] In the above preparation method, preferably, no gas is introduced during the calcination process.
[0027] In the above preparation method, preferably, the constant temperature of the calcination is 650-950°C, more preferably 700-900°C, and further preferably 750-850°C.
[0028] In the above preparation method, preferably, the heating rate of the calcination is 0.5 to 10°C / min, more preferably 1 to 8°C / min, and further preferably 2 to 5°C / min.
[0029] In the above preparation method, preferably, the constant temperature time of calcination is 30 to 180 min, more preferably 60 to 120 min.
[0030] A second aspect of the present invention provides a nitrogen-doped carbon-based composite electrode material, which is prepared by the above-mentioned method for preparing the nitrogen-doped carbon-based composite electrode material.
[0031] According to a specific embodiment of the present invention, preferably, the specific surface area of the nitrogen-doped carbon-based composite electrode material is 500 to 1500 m 2 / g, total pore volume is 0.3~1.5cm 3 / g, compacted density is 0.15~0.45g / cm 3 The mass content of nitrogen in the nitrogen-doped carbon-based composite electrode material is 2.5-12%.
[0032] The third aspect of the present invention provides the use of the above-mentioned nitrogen-doped carbon-based composite electrode material as a self-supporting electrode in an energy storage and conversion device.
[0033] In the above application, preferably, the energy storage and conversion device includes one or a combination of supercapacitors, lithium-sulfur batteries, lithium ion batteries, sodium ion batteries, lithium ion capacitors, sodium ion capacitors, potassium ion capacitors, and capacitor deionization devices, etc. More preferably, the energy storage and conversion device includes a double-layer capacitor and / or a capacitor deionization device, etc.
[0034] The present invention provides a nitrogen-doped carbon-based composite electrode material, a preparation method and an application thereof. The preparation method of the electrode material comprises compounding activated carbon, a conductive agent and a melamine sponge, and preparing the composite electrode material through a one-step calcination. The technical solution of the present invention solves the problems of the cumbersome preparation steps of the nitrogen-doped carbon-based self-supporting electrode in the prior art, low uniformity of nitrogen doping, insufficient mechanical strength of the electrode due to post-activation treatment, and low electrode density. The technical solution of the present invention can improve the nitrogen doping level of the electrode material, realize the self-supporting function of the electrode, and improve the mass transfer efficiency of the electrode.
[0035] The technical solution of the present invention has at least the following beneficial effects:
[0036] Beneficial effect 1: The composite electrode material has self-supporting properties
[0037] Traditional powdered activated carbon must be prepared by slurrying and current collector coating (such as aluminum foil, copper foil, nickel foam) to prepare electrodes, resulting in a heavier electrode weight and lower electrode mass specific capacity.
[0038] The present invention uses melamine sponge as a skeleton, anchors / embeds activated carbon and a conductive agent in the pores of the sponge, and directly prepares the electrode material through a one-step carbonization (calcination). The carbonized melamine sponge has a high mechanical strength and can realize elastic deformation of the electrode. At the same time, the activated carbon can play a role in filling, supporting, and reinforcing to prevent structural fracture and failure during the deformation of the sponge skeleton. The electrode material of the present invention does not require an additional metal current collector, and can greatly improve the mass specific capacity of the entire electrode.
[0039] Beneficial effect 2: Composite electrode materials have higher energy density
[0040] The composite electrode material of the present invention has a high volume density, which can further improve the volume capacity of the electrode. Moreover, the electrode material of the present invention can be used directly without further activation, thereby preventing the destruction of the melamine skeleton structure during the activation process.
[0041] Beneficial effect 3: The composite electrode material has a higher nitrogen doping level
[0042] In the present invention, melamine sponge is used as both a supporting skeleton and a nitrogen doping source for the composite electrode. During the calcination process of melamine sponge, pyrolysis generates a large amount of nitride gas (Study on Preparation of Carbon Nitrogen Precursor by Melamine Pyrolysis, Master's Thesis of Yanshan University, 2004). During the heating and constant temperature stages, the nitride gas released by pyrolysis of melamine overflows to the surface of the activated carbon and undergoes a nitrogen-carbon doping reaction at the calcination temperature, i.e., it forms a carbon-nitrogen bond structure with the carbon atoms in the pores of the activated carbon at high temperature, thereby achieving in-situ doping of the activated carbon with nitrogen.
[0043] Beneficial effect 4: Improved mass transfer efficiency of composite electrode materials
[0044] Melamine sponge has an extremely high porosity, and the pores are macroscopic pores (10-100 μm). Activated carbon is mainly microporous (<2 nm), and its adsorption capacity is large, but the mass transfer efficiency is low when used alone as an electrode material (Electronic Components and Materials, 2021, 40 (5): 406-413). The composite electrode of the present invention uses activated carbon as a filler and adsorbent, which is the main place for ion adsorption. Melamine sponge is used as a substrate skeleton, which is evenly combined between activated carbon particles. The capillary action produced quickly transfers ions to the surface of activated carbon particles, improves adsorption efficiency, and further improves the rate performance of the electrode.
[0045] In summary, the nitrogen-doped carbon-based composite electrode material and the preparation method thereof provided by the present invention can achieve the beneficial effects of improving electrode strength, improving nitrogen doping level, and improving ion transmission efficiency and thus improving mass transfer efficiency, rather than just a simple combination of the properties of each raw material. The nitrogen-doped carbon-based composite electrode material provided by the present invention can be used in energy storage and conversion fields involving electrical adsorption, including capacitor energy storage, capacitor deionization, and other scenarios requiring self-supporting electrodes and nitrogen-doped electrodes, and can especially exert better performance in double-layer capacitor electrodes and capacitor deionization device electrodes. Moreover, the nitrogen-doped carbon-based composite electrode material and the preparation method thereof provided by the present invention meet the industrial needs of low cost, uniform quality, and easy engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 A process roadmap for the preparation of nitrogen-doped carbon-based composite electrode materials provided for some specific embodiments of the present invention.
[0047] Figure 2 This is a physical photo of the composite electrode 1 provided in Example 1.
[0048] Figure 3 This is a photograph showing the anti-bending performance of the composite electrode 2 provided in Example 2.
[0049] Figure 4 This is a photograph showing the compression-rebound performance of the composite electrode 2 provided in Example 2.
[0050] Figure 5 Capacitive linear cyclic voltammetry curve of the composite electrode 1 provided in Example 1.
[0051] Figure 6 This is a capacitive AC impedance spectrum of the composite electrode 1 provided in Example 1.
[0052] Figure 7The adsorption-desorption isotherms of the composite electrode 1 provided in Example 1 and the comparative electrode 2 provided in Comparative Example 2. DETAILED DESCRIPTION
[0053] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0054] A first aspect of the present invention provides a method for preparing a nitrogen-doped carbon-based composite electrode material, which comprises the following steps:
[0055] The melamine sponge is immersed in a suspension formed by mixing activated carbon, a conductive agent, a binder and a solvent, and the immersed melamine sponge is dried to obtain a composite precursor; the composite precursor is calcined in an oxygen-free atmosphere, and the nitrogen-doped carbon-based composite electrode material is obtained after cooling;
[0056] Wherein, based on the total mass of activated carbon, conductive agent and binder as 100%, the amount of activated carbon is 50-93%, the amount of conductive agent is 2-30%, and the amount of binder is 5-20%.
[0057] In some preferred embodiments of the present invention, Figure 1 As shown, the method for preparing the nitrogen-doped carbon-based composite electrode material comprises the following steps:
[0058] (1) Preparation of suspension: uniformly mix and disperse the activated carbon, conductive agent, binder and solvent to form a suspension;
[0059] (2) impregnation: completely immersing the melamine sponge in the suspension to obtain an impregnated sponge;
[0060] (3) Drying: drying the impregnated sponge to remove the solvent and obtain a composite precursor;
[0061] (4) Carbonization: calcining the composite precursor in an oxygen-free atmosphere and, after cooling, obtaining the nitrogen-doped carbon-based composite electrode material.
[0062] In some specific embodiments, the density of the melamine sponge is 4 to 20 kg / m 3 The opening rate is 95-99.8%, and the average pore size is 10-100 μm.
[0063] In some specific embodiments, the melamine sponge may be washed, dried and cut before being impregnated. For example, in certain embodiments of the present invention, the melamine sponge is washed to remove impurities on its surface, and the washing solvent may include deionized water and / or ethanol, etc.; the drying temperature after washing may be conventionally selected by a person skilled in the art; and then, the melamine sponge is cut into a certain size, for example, into a melamine sponge of 2.0 cm×2.0 cm×0.5 cm (length×width×height) for standby use.
[0064] In some specific embodiments, the activated carbon may include one or a combination of biomass-based activated carbon, coal-based activated carbon, petroleum-based activated carbon, and the like.
[0065] In some specific embodiments, the specific surface area of the activated carbon is 200 to 4000 m 2 / g, particle size is 2-100 μm (measured in D50 diameter), and the pore volume of micropores with pore size less than 2 nm is 0.3-0.9 cm 3 / g, total pore volume is 0.3~1.5cm 3 / g. Preferably, the specific surface area of the activated carbon is 800 to 2000 m 2 / g, the particle size is 6-20 μm (measured in D50 diameter), and the pore volume of micropores with a pore size less than 2 nm is 0.45-0.8 cm 3 / g, total pore volume is 0.5~1.5cm 3 / g.
[0066] In some specific embodiments, the conductive agent includes one or a combination of carbon black, graphene, graphite, etc.
[0067] In some specific embodiments, the binder includes one or a combination of polyvinylidene fluoride, carboxymethyl cellulose, polytetrafluoroethylene, styrene-butadiene latex, polyvinyl alcohol, and the like.
[0068] In a specific embodiment of the present invention, as described above, the usage ratio of the activated carbon, the conductive agent, and the binder can be: 50-93% (mass percentage) of the activated carbon, 2-30% (mass percentage) of the conductive agent, and 5-20% (mass percentage) of the binder. For example, in certain embodiments of the present invention, 8g of activated carbon, 1g of carbon black (conductive agent), and 1g of polyvinylidene fluoride (binder) are taken, and the mass percentages of the three are 80%, 10%, and 10%, respectively.
[0069] In some specific embodiments, the solvent is not particularly limited as long as it is compatible with the binder. For example, in some embodiments of the present invention, if polyvinylidene fluoride is selected as the binder, nitrogen methyl pyrrolidone and / or dimethylformamide are preferably used as the solvent.
[0070] In some specific embodiments, the volume ratio of the solvent: the total amount of the activated carbon, the conductive agent and the binder may be 1:1 to 20:1.
[0071] In some specific embodiments, the solid content of the suspension is 5-50% by volume.
[0072] In some specific embodiments, step (1) specifically includes: weighing activated carbon, a conductive agent and a binder and placing them in a container, adding a solvent into the container, and uniformly mixing and dispersing the solid powder and the solvent to form a suspension.
[0073] In some specific embodiments, the uniform mixing and dispersing method includes stirring mixing, ultrasound-assisted mixing, vacuum-assisted mixing, etc., or a combination of several of them.
[0074] In some specific embodiments, the melamine sponge is immersed in the suspension by ultrasound-assisted dipping to make the dipping more uniform and sufficient.
[0075] In some specific embodiments, the melamine sponge is immersed in the suspension for 2 to 30 minutes.
[0076] In some specific embodiments, the mass ratio of the melamine sponge to the activated carbon in the suspension is 1:100 to 1:1000.
[0077] In some specific embodiments, in the composite precursor, the mass ratio of the melamine sponge to the activated carbon supported thereon is 1:0.5 to 1:10.
[0078] In some specific embodiments, the drying in step (3) includes freeze drying or oven drying.
[0079] In some specific embodiments, the calcination atmosphere is controlled to be an anaerobic atmosphere by placing the composite precursor in a calcination furnace, first using a vacuum system to evacuate the air in the calcination furnace, and then introducing a non-oxidizing gas to completely replace the air in the pores of the composite precursor. Preferably, the non-oxidizing gas may be introduced repeatedly for several times.
[0080] In some specific embodiments, the calcining furnace is not limited in form and structure as long as the temperature and atmosphere required for the process are achieved. For example, in some embodiments, a tubular carbonization furnace, a box-type carbonization furnace, a microwave carbonization furnace or a vacuum furnace may be used.
[0081] In some specific embodiments, step (4) specifically includes: placing the composite precursor in a calcining furnace, first using a vacuum system to evacuate the air in the calcining furnace, maintaining the pressure in the calcining furnace for a period of time so that the pressure is less than 60 kPa, and then introducing a non-oxidizing gas, repeating several times so that the air in the pores of the composite precursor is completely replaced; after the replacement is completed, disconnecting the vacuum system, disconnecting the introduction of the non-oxidizing gas; heating the calcining furnace, and maintaining it for a period of time after reaching the constant temperature of calcination; after the constant temperature stage is over, cooling the calcining furnace; after the cooling is over, the nitrogen-doped carbon-based composite electrode material is obtained. Among them, the effect of disconnecting the introduction of the non-oxidizing gas after the replacement is completed (that is, not introducing the gas during the calcination process) is that during the heating and constant temperature stages, the nitride gas released by the thermal decomposition of melamine overflows to the surface of the activated carbon, and a nitrogen-carbon doping reaction occurs at the calcination temperature.
[0082] In some specific embodiments, the non-oxidizing gas includes one or a combination of nitrogen, argon, carbon dioxide, helium, etc.
[0083] In some specific embodiments, the calcination process is preferably controlled by a programmable temperature control system.
[0084] In some specific embodiments, the constant temperature of calcination is 650-950°C, preferably 700-900°C, and more preferably 750-850°C.
[0085] In some specific embodiments, the heating rate of the calcination is 0.5 to 10° C. / min, preferably 1 to 8° C. / min, and more preferably 2 to 5° C. / min.
[0086] In some specific embodiments, the constant temperature time of calcination is 30 to 180 min, preferably 60 to 120 min.
[0087] In some specific embodiments, the temperature reduction is programmed, and the rate of the temperature reduction is 5-10° C. / min. Under this temperature reduction rate, it is possible to prevent excessive temperature reduction from damaging the structure of the composite electrode material.
[0088] A second aspect of the present invention provides a nitrogen-doped carbon-based composite electrode material, which is prepared by the above-mentioned method for preparing the nitrogen-doped carbon-based composite electrode material.
[0089] In some specific embodiments, the specific surface area of the nitrogen-doped carbon-based composite electrode material is 500 to 1500 m 2 / g, total pore volume is 0.3~1.5cm 3 / g, compacted density is 0.15~0.45g / cm 3 The mass content of nitrogen in the nitrogen-doped carbon-based composite electrode material is 2.5-12%.
[0090] In some specific embodiments, the nitrogen-doped carbon-based composite electrode material has a specific capacitance of 156 F / g or more in a 6 mol / L potassium hydroxide solution electrolyte at a current density of 1 A / g.
[0091] The technical scheme of the present invention is specifically described below through examples and comparative examples, but the present invention is not limited to these examples and can of course be implemented in various modifications within the scope of the gist of the present invention.
[0092] The raw materials used in the embodiments and comparative examples include:
[0093] Activated carbon a: Specific surface area is about 1600m 2 / g, particle size 10-12 μm (measured in D50 diameter), pore volume of micropores with pore size less than 2 nm is 0.6 cm 3 / g, with a total pore volume of 0.85 cm 3 / g;
[0094] Activated carbon b: Specific surface area is about 900m 2 / g, particle size 14-20 μm (measured in D50 diameter), pore volume of micropores with pore size less than 2 nm is 0.45 cm 3 / g, with a total pore volume of 1.2 cm 3 / g;
[0095] Activated carbon c: Specific surface area of about 1800m 2 / g, particle size 6-10 μm (measured by D50 diameter), pore volume of micropores with pore size less than 2 nm is 0.66 cm 3 / g, and the total pore volume is 1.06cm 3 / g;
[0096] Melamine sponge a: density 8kg / m 3 , opening rate 99%;
[0097] Melamine sponge b: density 16kg / m 3 , opening rate 98%;
[0098] Conductive agent a: carbon black, purchased from Lion Corporation of Japan, model: CEP600 JD;
[0099] Conductive agent b: graphene, purchased from Xianfeng Nano Co., Ltd., model: XF021;
[0100] Conductive agent c: graphite, purchased from McLean Reagent Co., Ltd., model: 99.95% METALS BASIS, 8000 mesh;
[0101] Binder a: polyvinylidene fluoride, purchased from Sinopharm Chemical Reagent Co., Ltd., purity > 95%;
[0102] Binder b: carboxymethyl cellulose, purchased from Sinopharm Chemical Reagent Co., Ltd., purity > 98%;
[0103] Binder c: polytetrafluoroethylene, purchased from Sinopharm Chemical Reagent Co., Ltd., purity > 98%.
[0104] The analysis and testing methods used in the embodiments and comparative examples include:
[0105] 1. Specific surface area, pore volume and average pore size of electrode materials: The multi-point BET adsorption method is used, with specific reference to the method described in GB / T19587. For ease of comparison, the specific surface area is tested based on the overall electrode.
[0106] 2. Compacted density of electrode materials: Tested according to the method described in GB / T 24533.
[0107] 3. Analysis of element content of electrode materials: measured using an element analyzer.
[0108] 4. Analysis of electrochemical properties of electrode materials:
[0109] Device assembly: The electrochemical performance was evaluated using a symmetrical double-electrode capacitor. The two symmetrical electrodes were loaded with the same mass of active material. A 6 mol / L potassium hydroxide solution was used as the electrolyte. The diaphragm was glass fiber (Whatman, GF / D1823-047). The capacitor was assembled using a CR2032 button battery shell.
[0110] The cyclic voltammetry test, specific capacitance test, and AC impedance test all refer to the methods described in IEC 62391-1-2015;
[0111] The specific capacitance (C) is calculated based on the mass of the electrode and follows the following formula:
[0112]
[0113] Wherein, I (A) is the discharge current; Δt (s) is the discharge time; m (g) is the mass of activated carbon in the electrode; ΔV (V) is the voltage window of the discharge interval. In the tests of the embodiments and comparative examples of the present invention, ΔV = 1.0V.
[0114] Example 1
[0115] This embodiment provides a nitrogen-doped carbon-based composite electrode material, and the preparation method thereof comprises the following steps:
[0116] (1) 8 g of activated carbon a, 1 g of conductive agent a (carbon black), 1 g of binder a (polyvinylidene fluoride) and 120 mL of nitrogen methyl pyrrolidone were added to a stirring tank and stirred to mix uniformly to obtain a uniform suspension;
[0117] (2) washing and drying the melamine sponge a, and then cutting it into a size of 2.0 cm×2.0 cm×0.5 cm, and completely immersing the melamine sponge in the suspension, using an ultrasonic-assisted immersion method, and fully immersing it for 10 minutes to obtain an impregnated sponge, which is then taken out;
[0118] (3) drying the impregnated sponge at 80° C. for 5 h to remove the solvent and obtain a composite precursor, in which the mass ratio of melamine sponge to activated carbon is about 1:2.5;
[0119] (4) The composite precursor is placed in a tubular furnace, and the air in the furnace is first evacuated using a vacuum system, and the pressure in the furnace is maintained for a period of time so that the pressure in the furnace is less than 60 kPa. Nitrogen is introduced to replace the air in the furnace three times, so that the air in the pores of the composite precursor is completely replaced; after the replacement is completed, the connection with the vacuum system is disconnected, the nitrogen introduction is disconnected, and the temperature is increased to 800°C at a heating rate of 2°C / min, and this temperature is maintained for 120 minutes, and then cooled to room temperature at a cooling rate of 5°C / min. The calcined product is taken out and directly cut into electrodes with a size of 0.8 cm×0.8 cm×0.1 cm without further treatment to obtain a nitrogen-doped carbon-based composite electrode material, which is recorded as composite electrode 1.
[0120] The effective adsorbent (i.e., activated carbon) loading of the composite electrode 1 is 2.65 mg, and the electrode area is 0.64 cm 2 , then its unit load is 4.14 mg / cm 2 The effective adsorbent loading is calculated by subtracting the mass of the material prepared without adding activated carbon in step (1) (ie, comparative example 1) to obtain the effective adsorbent loading.
[0121] Figure 2 is a real photo of the composite electrode 1.
[0122] Example 2
[0123] This embodiment provides a nitrogen-doped carbon-based composite electrode material, and the preparation method thereof comprises the following steps:
[0124] (1) 8 g of activated carbon a, 1 g of conductive agent a (carbon black), 1 g of binder a (polyvinylidene fluoride) and 200 mL of nitrogen methyl pyrrolidone were added to a stirring tank and stirred to mix uniformly to obtain a uniform suspension;
[0125] (2) washing and drying the melamine sponge a, and then cutting it into a size of 5.0 cm×5.0 cm×1.0 cm, and completely immersing the melamine sponge in the suspension, using an ultrasonic-assisted immersion method, and fully immersing it for 10 minutes to obtain an impregnated sponge, which is then taken out;
[0126] (3) drying the impregnated sponge at 80° C. for 5 h to remove the solvent and obtain a composite precursor, in which the mass ratio of melamine sponge to activated carbon is about 1:1.8;
[0127] (4) The composite precursor is placed in a tubular furnace, and the air in the furnace is first evacuated using a vacuum system, and the pressure in the furnace is maintained for a period of time so that the pressure in the furnace is less than 60 kPa, and nitrogen is introduced to replace the air in the furnace, so that the air in the pores of the composite precursor is completely replaced; after the replacement is completed, the connection with the vacuum system is disconnected, the nitrogen introduction is disconnected, and the temperature is increased to 750°C at a heating rate of 2°C / min, and this temperature is maintained for 120 minutes, and then cooled to room temperature at a cooling rate of 5°C / min, and the calcined product is taken out and directly cut into electrodes with a size of 1.0 cm×1.0 cm×0.2 cm without further treatment to obtain a nitrogen-doped carbon-based composite electrode material, which is recorded as composite electrode 2.
[0128] Figure 3 The anti-bending performance of the composite electrode 2 is demonstrated. Figure 3 It can be seen that the composite electrode 2 does not break after being bent at 90 degrees and 150 degrees, and has good self-supporting mechanical properties.
[0129] Figure 4 The compression-rebound performance of the composite electrode 2 is shown. Figure 4 It can be seen that after being compressed by a weight of 200 g, the composite electrode 2 can recover to its initial state and has good self-supporting mechanical properties.
[0130] Example 3
[0131] This embodiment provides a nitrogen-doped carbon-based composite electrode material, and the preparation method thereof comprises the following steps:
[0132] (1) 9 g of activated carbon b, 0.2 g of conductive agent b (graphene), 0.8 g of binder b (carboxymethyl cellulose) and 100 mL of water were added to a stirring tank and stirred to mix well to obtain a uniform suspension;
[0133] (2) washing and drying the melamine sponge a, and then cutting it into a size of 2.0 cm×2.0 cm×0.5 cm, and completely immersing the melamine sponge in the suspension, using an ultrasonic-assisted immersion method, and fully immersing it for 25 minutes to obtain an impregnated sponge, which is then taken out;
[0134] (3) drying the impregnated sponge at 80° C. for 8 h to remove the solvent and obtain a composite precursor, in which the mass ratio of melamine sponge to activated carbon is about 1:3.2;
[0135] (4) The composite precursor is placed in a tubular furnace, and the air in the furnace is first evacuated using a vacuum system, and the pressure in the furnace is maintained for a period of time so that the pressure in the furnace is less than 60 kPa. Nitrogen is introduced to replace the air in the furnace three times, so that the air in the pores of the composite precursor is completely replaced; after the replacement is completed, the connection with the vacuum system is disconnected, the nitrogen introduction is disconnected, and the temperature is increased to 850°C at a heating rate of 5°C / min, and this temperature is maintained for 60 minutes, and then the temperature is cooled to room temperature at a cooling rate of 5°C / min. The calcined product is taken out and directly cut into electrodes with a size of 1.5 cm×1.5 cm×0.1 cm without further treatment to obtain a nitrogen-doped carbon-based composite electrode material, which is recorded as composite electrode 3.
[0136] Example 4
[0137] This embodiment provides a nitrogen-doped carbon-based composite electrode material, and the preparation method thereof comprises the following steps:
[0138] (1) Add 6 g of activated carbon b, 3 g of conductive agent b (graphene), 1 g of binder b (carboxymethyl cellulose) and 80 mL of water into a stirring tank, stir and mix well to obtain a uniform suspension;
[0139] (2) washing and drying the melamine sponge b, and then cutting it into a size of 2.0 cm×2.0 cm×0.5 cm, and completely immersing the melamine sponge in the suspension, using an ultrasonic-assisted immersion method, and fully immersing it for 5 minutes to obtain an impregnated sponge, which is then taken out;
[0140] (3) drying the impregnated sponge at 80° C. for 8 h to remove the solvent and obtain a composite precursor, in which the mass ratio of melamine sponge to activated carbon is about 1:1.3;
[0141] (4) The composite precursor is placed in a tubular furnace, and the air in the furnace is first evacuated using a vacuum system, and the pressure in the furnace is maintained for a period of time so that the pressure in the furnace is less than 60 kPa. Nitrogen is introduced to replace the air in the furnace three times, so that the air in the pores of the composite precursor is completely replaced; after the replacement is completed, the vacuum system is disconnected, the nitrogen introduction is disconnected, and the temperature is increased to 820°C at a heating rate of 5°C / min, and this temperature is maintained for 90 minutes, and then the temperature is cooled to room temperature at a cooling rate of 5°C / min. The calcined product is taken out and directly cut into electrodes with a size of 0.5 cm×0.5 cm×0.1 cm without further treatment to obtain a nitrogen-doped carbon-based composite electrode material, which is recorded as composite electrode 4.
[0142] Example 5
[0143] This embodiment provides a nitrogen-doped carbon-based composite electrode material, and the preparation method thereof comprises the following steps:
[0144] (1) 7.5 g of activated carbon a, 0.5 g of conductive agent c (graphite), 1 g of conductive agent a (carbon black), 1 g of binder b (carboxymethyl cellulose) and 100 mL of water were added to a stirring tank and stirred to mix well to obtain a uniform suspension;
[0145] (2) washing and drying the melamine sponge a, and then cutting it into a size of 3.0 cm×3.0 cm×0.5 cm, and completely immersing the melamine sponge in the suspension, using an ultrasonic-assisted immersion method, and fully immersing it for 5 minutes to obtain an impregnated sponge, which is then taken out;
[0146] (3) drying the impregnated sponge at 80° C. for 8 h to remove the solvent and obtain a composite precursor, in which the mass ratio of melamine sponge to activated carbon is about 1:2.2;
[0147] (4) The composite precursor is placed in a tubular furnace, and the air in the furnace is first evacuated using a vacuum system, and the pressure in the furnace is maintained for a period of time so that the pressure in the furnace is less than 60 kPa. Nitrogen is introduced to replace the air in the furnace three times, so that the air in the pores of the composite precursor is completely replaced; after the replacement is completed, the connection with the vacuum system is disconnected, the nitrogen introduction is disconnected, and the temperature is increased to 820°C at a heating rate of 3°C / min, and this temperature is maintained for 60 minutes, and then the temperature is cooled to room temperature at a cooling rate of 5°C / min. The calcined product is taken out and directly cut into electrodes with a size of 1 cm×1 cm×0.1 cm without further treatment to obtain a nitrogen-doped carbon-based composite electrode material, which is recorded as composite electrode 5.
[0148] Example 6
[0149] This embodiment provides a nitrogen-doped carbon-based composite electrode material, and the preparation method thereof comprises the following steps:
[0150] (1) 8 g of activated carbon c, 1 g of conductive agent b (graphene), 1 g of binder c (polytetrafluoroethylene) and 100 mL of nitrogen methyl pyrrolidone were added to a stirring tank and stirred to mix uniformly to obtain a uniform suspension;
[0151] (2) washing and drying the melamine sponge b, and then cutting it into a size of 5.0 cm×5.0 cm×1.0 cm, and completely immersing the melamine sponge in the suspension, using an ultrasonic-assisted immersion method, and fully immersing it for 3 minutes to obtain an impregnated sponge, which is then taken out;
[0152] (3) drying the impregnated sponge at 60° C. for 10 h to remove the solvent and obtain a composite precursor, in which the mass ratio of melamine sponge to activated carbon is about 1:1.6;
[0153] (4) The composite precursor is placed in a tubular furnace, and the air in the furnace is first evacuated using a vacuum system, and the pressure in the furnace is maintained for a period of time so that the pressure in the furnace is less than 40 kPa. Argon gas is introduced to replace the air in the furnace three times, so that the air in the pores of the composite precursor is completely replaced; after the replacement is completed, the connection with the vacuum system is disconnected, the introduction of argon gas is disconnected, and the temperature is increased to 780°C at a heating rate of 2°C / min, and this temperature is maintained for 120 minutes, and then cooled to room temperature at a cooling rate of 5°C / min. The calcined product is taken out and directly cut into electrodes with a size of 1 cm×1 cm×0.1 cm without further treatment to obtain a nitrogen-doped carbon-based composite electrode material, which is recorded as composite electrode 6.
[0154] Comparative Example 1
[0155] This comparative example provides a nitrogen-doped carbon-based electrode material, and its preparation method is basically the same as that of Example 1, except that: no activated carbon is added, and the obtained electrode material is named comparative electrode 1.
[0156] Comparative Example 2
[0157] This comparative example provides an electrode material, and its preparation method comprises the following steps:
[0158] Take 8 g of activated carbon a, 1 g of conductive agent a (carbon black), 1 g of binder a (polyvinylidene fluoride) and 120 mL of nitrogen methyl pyrrolidone, add them into a stirring tank, stir and mix evenly to obtain a uniform suspension; take a 30 cm × 10 cm aluminum foil with a thickness of 18 μm, and evenly coat the suspension on the aluminum foil by a coating machine and dry it. During the coating process, adjust the coating thickness so that the loading of effective adsorbent (i.e., activated carbon) per unit area is the same as that in Example 1, i.e., 4.14 mg / cm 2 , and then cut into aluminum foil-based electrode materials with a size of 0.8 cm × 0.8 cm, named comparative electrode 2.
[0159] Comparative Example 3
[0160] This comparative example provides a nitrogen-doped carbon-based composite electrode material, and the preparation method thereof comprises the following steps:
[0161] 1 g of melamine powder and 8 g of activated carbon a were uniformly mixed in an appropriate amount of nitrogen methyl pyrrolidone, and after drying, the mixed powder was placed in a tube furnace, and the air in the furnace was first evacuated using a vacuum system, and the pressure in the furnace was maintained for a period of time to be less than 60 kPa, and nitrogen was introduced to replace the air in the furnace for 3 times; after the replacement was completed, the vacuum system was disconnected, the nitrogen was disconnected, and the temperature was increased to 750°C at a rate of 2°C / min, and this temperature was maintained for 120 minutes, and then the temperature was reduced to room temperature at a rate of 5°C / min, and the calcined product was taken out; The calcined product, 1 g of conductive agent a (carbon black), 1 g of binder a (polyvinylidene fluoride) and 120 ml of nitrogen methyl pyrrolidone were added to a stirring tank and stirred to mix uniformly to obtain a uniform suspension; a 30 cm × 10 cm aluminum foil with a thickness of 18 μm was taken, and the suspension was evenly coated on the aluminum foil by a coating machine and dried. During the coating process, the coating thickness was adjusted so that the loading of effective adsorbent (i.e., activated carbon) per unit area was the same as that in Example 1, i.e., 4.14 mg / cm 2 , and then cut into aluminum foil-based electrode materials with a size of 0.8 cm×0.8 cm, named comparative electrode 3.
[0162] Test Case
[0163] The electrode materials of Examples 1 to 6 and Comparative Examples 1 to 3 were tested for specific surface area, pore volume and average pore diameter, compaction density, nitrogen content, and electrochemical performance. The results are shown in Tables 1 and 2. Figures 5 to 7 shown. Figure 5 Capacitive linear cyclic voltammetry curve of the composite electrode 1 provided in Example 1. Figure 6 This is a capacitive AC impedance spectrum of the composite electrode 1 provided in Example 1. Figure 7 The adsorption-desorption isotherms of the composite electrode 1 provided in Example 1 and the comparative electrode 2 provided in Comparative Example 2.
[0164] Table 1
[0165]
[0166] By comparing Comparative Example 1 with Examples 1 to 6, it can be seen that no activated carbon is added to Comparative Example 1, and the specific surface area of the obtained electrode is extremely low, resulting in a lower capacity. The nitrogen-doped carbon-based composite electrode material provided in Examples 1 to 6 has a specific capacitance of more than 156F / g in a 6mol / L potassium hydroxide solution electrolyte at a current density of 1A / g, and Example 6 can reach 188F / g; while the specific capacitance of Comparative Example 1 is only 32F / g under the same test conditions. At the same time, the nitrogen element retention of the electrode of Comparative Example 1 is relatively small. However, due to the three-dimensional porous structure of the melamine sponge, the ion transmission efficiency of the electrode of Comparative Example 1 is relatively high, that is, the capacity retention rate when the charge and discharge current reaches 20A / g is still significantly higher than that of the electrodes prepared using traditional methods in Comparative Examples 2 and 3.
[0167] By comparing Comparative Example 2 with Examples 1 to 6, it can be seen that Comparative Example 2 uses traditional metal foil to prepare electrodes by coating, and its overall specific surface area is lower than that of Example 1. Due to the lack of nitrogen doping, its capacity is lower than that of Example 1. At the same time, the rate performance (i.e., the capacitance retention rate under high current) of the electrode prepared by traditional coating in Comparative Example 2 is about 20% lower than that of the three-dimensional electrode composed of melamine sponge-activated carbon, etc. in Example 1. It can also be seen that the composite electrodes of Examples 1 to 6 have higher mass transfer efficiency. Figure 7 The difference in mass transfer efficiency between Example 1 and Comparative Example 2 is revealed from the perspective of pore structure. Figure 7 It can be seen that the composite electrode 1 of Example 1 has a larger hysteresis loop area and a larger adsorption increment at a relative pressure of 0.2-1.0, indicating more mesopores in its electrode structure, especially in the relative pressure range of 0.9-1.0, where there is a significant adsorption increment, which is attributed to the pores formed between the melamine sponge skeleton and the activated carbon particles.
[0168] By comparing Comparative Example 3 with Examples 1 to 6, it can be seen that Comparative Example 3 uses a traditional nitrogen source to mix and prepare electrodes. Although it can achieve doping of nitrogen elements, its doping level, specific surface area, capacity, etc. still cannot reach the electrode level of the embodiments of the present invention. Most importantly, the electrode material prepared by the common nitrogen source is still a powder structure, which depends on coating on the metal current collector to be used as an electrode, that is, it naturally cannot provide self-supporting ability and the unique high-efficiency mass transfer ability brought by the melamine sponge (the specific capacitance retention rate of Comparative Example 3 is significantly reduced compared with Examples 1 to 6). At the same time, based on Comparative Example 3, if other nitrogen sources known in the industry, such as urea, etc., are used, because they also do not have the special structure of the melamine sponge in the present invention, the excellent performance of the embodiments of the present invention cannot be achieved.
[0169] In summary, the present invention achieves a higher nitrogen doping amount through a relatively simple preparation method, while achieving self-support of the electrode and improving the mass transfer efficiency.
[0170] The nitrogen-doped carbon-based composite electrode material provided by the present invention can be used as a self-supporting electrode in energy storage and conversion devices, for example, in supercapacitors, lithium-sulfur batteries, lithium ion batteries, sodium ion batteries, lithium ion capacitors, sodium ion capacitors, potassium ion capacitors and capacitor deionization devices.
Claims
1. A method for preparing a nitrogen-doped carbon-based composite electrode material, comprising the following steps: The melamine sponge is immersed in a suspension formed by mixing activated carbon, a conductive agent, a binder and a solvent, and the immersed melamine sponge is dried to obtain a composite precursor; the composite precursor is calcined in an oxygen-free atmosphere, and the nitrogen-doped carbon-based composite electrode material is obtained after cooling; Wherein, based on the total mass of activated carbon, conductive agent and binder as 100%, the amount of activated carbon is 50-93%, the amount of conductive agent is 2-30%, and the amount of binder is 5-20%.
2. The preparation method according to claim 1, wherein The density of the melamine sponge is 4 to 20 kg / m 3 The opening rate is 95-99.8%.
3. The preparation method according to claim 1, wherein The specific surface area of the activated carbon is 200 to 4000 m 2 / g, particle size is 2-100 μm, pore volume of micropores with pore size less than 2 nm is 0.3-0.9 cm 3 / g, total pore volume is 0.3~1.5cm 3 / g; Preferably, the specific surface area of the activated carbon is 800 to 2000 m 2 / g, particle size is 6-20μm, pore volume of micropores with pore size less than 2nm is 0.45-0.8cm 3 / g, total pore volume is 0.5~1.5cm 3 / g.
4. The preparation method according to claim 1, wherein The conductive agent includes one or a combination of carbon black, graphene and graphite.
5. The preparation method according to claim 1, wherein The binder includes one or a combination of polyvinylidene fluoride, carboxymethyl cellulose, polytetrafluoroethylene, styrene-butadiene latex and polyvinyl alcohol.
6. The preparation method according to claim 1, wherein In terms of volume percentage, the solid content of the suspension is 5-50%.
7. The preparation method according to claim 1, wherein The activated carbon, the conductive agent, the binder and the solvent are uniformly mixed and dispersed to form a suspension, wherein the uniform mixing and dispersion method includes stirring mixing, ultrasound-assisted mixing and vacuum-assisted mixing, or a combination of the two.
8. The preparation method according to claim 1, wherein The melamine sponge is immersed in the suspension by ultrasonic assisted dipping; Preferably, the melamine sponge is immersed in the suspension for 2 to 30 minutes; Preferably, the mass ratio of the melamine sponge to the activated carbon in the suspension is 1:100 to 1:1000; Preferably, in the composite precursor, the mass ratio of melamine sponge to activated carbon is 1:0.5 to 1:
10.
9. The preparation method according to claim 1, wherein The method of controlling the calcination atmosphere to be an anaerobic atmosphere includes: placing the composite precursor in a calcination furnace, first using a vacuum system to evacuate the air in the calcination furnace, and then introducing a non-oxidizing gas to completely replace the air in the pores of the composite precursor; Preferably, the non-oxidizing gas includes one or a combination of nitrogen, argon, carbon dioxide and helium.
10. The preparation method according to claim 1, wherein: No gas is introduced during the calcination process; Preferably, the calcination temperature is 650-950°C; Preferably, the heating rate of the calcination is 0.5 to 10°C / min; Preferably, the constant temperature time of calcination is 30 to 180 minutes.
11. A nitrogen-doped carbon-based composite electrode material, which is prepared by the method for preparing a nitrogen-doped carbon-based composite electrode material according to any one of claims 1 to 10; Preferably, the specific surface area of the nitrogen-doped carbon-based composite electrode material is 500 to 1500 m 2 / g, total pore volume is 0.3~1.5cm 3 / g, compacted density is 0.15~0.45g / cm 3 The mass content of nitrogen in the nitrogen-doped carbon-based composite electrode material is 2.5-12%.
12. Use of the nitrogen-doped carbon-based composite electrode material according to claim 11 as a self-supporting electrode in an energy storage and conversion device; Preferably, the energy storage and conversion device comprises one or a combination of supercapacitors, lithium-sulfur batteries, lithium ion batteries, sodium ion batteries, lithium ion capacitors, sodium ion capacitors, potassium ion capacitors and capacitive deionization devices.
Citation Information
Patent Citations
Nitrogen-doped carbon flexible paper and preparing method and application thereof
CN105826562A
Flexible three-dimensional porous carbon material and preparation method and application thereof
CN108074751A
Activated sponge capacitor material as well as preparation method and application thereof
CN113223862A
Preparation method and application of lithium-sulfur battery three-dimensional carbon current collector
CN105489901A
Synthesis method of special crosslinked hollow spherical nitrogen-doped carbon material
CN106219515A